Effect of feeding frequency and adding Moringa seeds to the ration on growth traits and some blood components in Awassi lambs - Hayder, Israa Salim; Abdullah, Muthanna Fathi (Journal of agricultural, environmental and veterinary sciences, 2023)
The study included 24 Awassi lambs aged of (3-4) months, applied in four treatments, the first treatment was fed twice daily without supplementation, the second treatment was fed twice daily with the addition of 5 gm of moringa seeds/head/day, the third treatment was fed three times daily without supplementation, and the fourth treatment They were fed three times daily with the addition of 5 gm of moringa seeds/head/day. Lambs were distributed randomly to the four treatments so that they were homogeneous in weight. Each treatment included 6 lambs. The aim of the study was the effect of feed frequency and the addition of moringa seeds to ration on growth traits and some biochemical components of blood in Awassi lambs. The results of the study showed that the fourth treatment was significantly superior (p≤ 0.05) in final weight and total weight gain compared to the second and third treatments. The best food conversion efficiency appeared in the fourth treatment, which was fed three times with the addition of moringa. Lambs that were fed three times a day were significantly (p≤ 0.05) superior to their counterparts that were fed twice a day in final weight and body length. The fourth overlap treatment was significantly (p≤ 0.01) superior in body length over the rest of the other treatments. A significant increase (p≤ 0.05) was observed in urea concentration during the second month in favor of the lambs that were fed three times a day. A significant high (p≤ 0.05) was observed in the concentration of cholesterol in the blood of the lambs that were fed three times a day with the addition of moringa compared to the rest of the other treatments during the third month of the study, while there were no significant differences in the rest of the other blood components. *The article is taken from a master’s thesis by the first researcher.